Monoclonal antibodies for cancer: a focus on mechanisms of action - Hardik Gandhi; Ramachandran Balaraman (Journal of Integrated Health Sciences)
Monoclonal antibodies (mAbs) have found several therapeutic applications. By Far, the most promising utilization of mAbs has been use of these agents in cancer therapeutics. The major reason for this is the ability of mAbs to selectively home-in on cancer cells opening up avenues for targeted therapy. The importance of mAbs for therapeutics can be recognized from the fact that more than 40 mAbs have been approved by the FDA till date for application in several disease modalities. Production of mAbs has also radical changes from the conventional methods till date. In relation to cancer, bevacizumab, trastuzumab and cetuximab may be considered as breakthroughs, significantly improving the therapeutic armamentarium against various types of cancers. This review focuses upon the current global status of mAbs in clinical studies with a convergence on different mechanisms of actions governing their therapeutic activity.